Improving patients' experience and outcome of total joint replacement: the RESTORE programme - Ashley W Blom; Neil Artz; Andrew D Beswick; Amanda Burston; Paul Dieppe; Karen T Elvers; Rachael Gooberman-Hill; Jeremy Horwood; Paul Jepson; Emma Johnson; Erik Lenguerrand; Elsa Marques; et al. (NIHR Journals Library, 2016)
Background: Total hip replacements (THRs) and total knee replacements (TKRs) are common elective procedures. In the REsearch STudies into the ORthopaedic Experience (RESTORE) programme, we explored the care and experiences of patients with osteoarthritis after being listed for THR and TKR up to the time when an optimal outcome should be expected. Objective: To undertake a programme of research studies to work towards improving patient outcomes after THR and TKR. Methods: We used methodologies appropriate to research questions: systematic reviews, qualitative studies, randomised controlled trials (RCTs), feasibility studies, cohort studies and a survey. Research was supported by patient and public involvement. Results: Systematic review of longitudinal studies showed that moderate to severe long-term pain affects about 7-23% of patients after THR and 10-34% after TKR. In our cohort study, 10% of patients with hip replacement and 30% with knee replacement showed no clinically or statistically significant functional improvement. In our review of pain assessment few research studies used measures to capture the incidence, character and impact of long-term pain. Qualitative studies highlighted the importance of support by health and social professionals for patients at different stages of the joint replacement pathway. Our review of longitudinal studies suggested that patients with poorer psychological health, physical function or pain before surgery had poorer long-term outcomes and may benefit from pre-surgical interventions. However, uptake of a pre-operative pain management intervention was low. Although evidence relating to patient outcomes was limited, comorbidities are common and may lead to an increased risk of adverse events, suggesting the possible value of optimising pre-operative management. The evidence base on clinical effectiveness of pre-surgical interventions, occupational therapy and physiotherapy-based rehabilitation relied on small RCTs but suggested short-term benefit. Our feasibility studies showed that definitive trials of occupational therapy before surgery and post-discharge group-based physiotherapy exercise are feasible and acceptable to patients. Randomised trial results and systematic review suggest that patients with THR should receive local anaesthetic infiltration for the management of long-term pain, but in patients receiving TKR it may not provide additional benefit to femoral nerve block. From a NHS and Personal Social Services perspective, local anaesthetic infiltration was a cost-effective treatment in primary THR. In qualitative interviews, patients and health-care professionals recognised the importance of participating in the RCTs. To support future interventions and their evaluation, we conducted a study comparing outcome measures and analysed the RCTs as cohort studies. Analyses highlighted the importance of different methods in treating and assessing hip and knee osteoarthritis. There was an inverse association between radiographic severity of osteoarthritis and pain and function in patients waiting for TKR but no association in THR. Different pain characteristics predicted long-term pain in THR and TKR. Outcomes after joint replacement should be assessed with a patient-reported outcome and a functional test. Conclusions: The RESTORE programme provides important information to guide the development of interventions to improve long-term outcomes for patients with osteoarthritis receiving THR and TKR. Issues relating to their evaluation and the assessment of patient outcomes are highlighted. Potential interventions at key times in the patient pathway were identified and deserve further study, ultimately in the context of a complex intervention. Study registration: Current Controlled Trials ISRCTN52305381. Funding: This project was funded by the NIHR Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 4, No. 12. See the NIHR Journals Library website for further project information.